OA in the UK: State of the nation - Rumsey, S (Cambridge University Press, 2016)
This paper provides an overview of the current status of UK national open access (OA) policies, their implementation, and the responses of HEIs (Higher Education Institutions) and other key players. Prior to 2012 a number of funders’ OA policies had been published. Although many medical scientists were publishing OA articles and subject pre-print repositories were active in some disciplines (for example ArXiv and RePEc EconPapers), most academics were not complying with their funder’s OA policy, the policies were not being policed, and in many disciplines, OA was not on researchers’ radar. The article concludes that OA in the UK has changed considerably in recent years and is continuing to evolve rapidly, mainly due to the effect of UK funder OA policies. There is an urgent need for increased automation to support greater accuracy and efficiency which needs input from, and will benefit, the major players: researchers, universities, funders and publishers. Sustainable funding needs to be coupled with efforts to drive down costs. The reasons behind the push for OA needs discussion with researchers, some of whom view OA as an additional burden. The value placed on OA needs to be weighted more towards the benefits of OA within a less compliance dominated environment. There is a long way to go, but reflecting on the last 4 years, the UK has made enormous strides towards widespread OA.